Efektifitas Metode Elektrokoagulasi Dengan Penambahan Medan Magnet Dalam Menyisihkan TSS dan COD Air Limbah Industri Rumah Potong Hewan - Cahyani, Nurilita Amalia; Rosariawari, Firra (Jurnal Serambi Engineering, 2025)
Slaughterhouse effluent is high in organic matter and suspended solids and requires treatment before direct discharge. We are combining electrocoagulation technology and magnetic fields as a treatment method to assess their impact on the effectiveness of TSS and COD removal. The aim of this study is to determine the effect of current strength and treatment contact time on the pH of the effluent and the efficiency of TSS and COD removal from slaughterhouse effluent. The variables in this study include current strengths of 1 ampere, 3 amperes and 5 amperes with treatment contact times of 30 minutes, 60 minutes, 90 minutes and 120 minutes. From the results of electrocoagulation experiments with and without a magnetic field, it is known that the magnetic field has the ability to accelerate the sedimentation process and remove suspended solids more effectively. The pH of the effluent increased with each increase in current and contact time. The best removal results were obtained in the electrocoagulation process with a magnetic field, which had a TSS removal of 96.06% and a COD removal of 89.37% at a pH of 8.3, using a current of 3 amperes and a contact time of 120 minutes.